Oral acetaminophen administration for patent ductus arteriosus (PDA) closure in preterm neonates - Mahmood Samadi; Zahra Nabaee; Manizheh Mostafagharebaghi; Majid Mahalei; Elham Sheykhsaran; Kayvan Mirnia (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2021)
Background: Patent Ductus Arteriosus (PDA) is considered one of the most prevalent types of congenital heart disease. The closure of the ductus arteriosus physiologically occurs at the first 48-72 hours after the birth in healthy term infants. Different causes can result in the pathological opening of ductus arteriosus. This study aims to investigate the effect of oral acetaminophen on the closure of PDA in preterm neonates. Methods: The present study is a trial without control. Forty-five preterm neonates with a gestational age of <32 weeks were studied. Acetaminophen was orally administered with a dose of 10mg/kg every 6 hours for three days. Closure of ductus arteriosus was considered as the success of treatment. Data were analyzed using SPSS 15. Data were reported as )frequency-percent) and mean ± SD. To evaluate the normal distribution of data, we used a Kolmogorov-Smirnov test. Statistical significance was defined as P<0.05. Results: The study population consisted of 20 male and 25 female infants with the mean gestational age of 28.95 ± 1.66 weeks. Cesarean-born infants and vaginal-born infants consisted 17.8% and 82.2% of the study population, respectively. The proportion of PDA closure after administration of oralacetaminophen was 82.3%. Conclusion: The current study indicates that oral acetaminophen is highly effective in closing PDA. Considering its trivial side effects, it has the potency to be a convenient option for treating this condition.